PERANAN KECAMATAN DALAM PENYELENGGARAAN OTONOMI DAERAH - Ali, Zaini (UIR PRESS, 2017)
Paradigm used in UU Number 32 Year 2004 about area Governance keanekaragamaan in union. That paradigm born not because of its ethnical problem multi [is] tribe, but also each;every area have the power of and at one blow the feebleness, good from geographical, experienced sumberdaya and the human being, and also geopolitics [of] when confronted with a democratization era as consequence applying of principality desentraliasi in governance. In consequence semenjak Indonesian nation enter Reform era giving space which broader relative if/when compared to by UU New Order era, solvable society problem by society xself pursuant to Autonomous principles [of] Area. In line with autonomous policy the area through Section 126 and 127 UU Number 32 Soybean cake 2004 sub-regency chief given two kewenangan at one blow, that is attributive kewenangan and kewenangan delegatif. Where [at] area to arrange and manage [his/its] own domestic. As for target given kewenangan [of] [Mayor or Regent to overflow some of governance business becoming [his/its] tangggung reply [is] in order to giving sense of justice [of] [at] society to get service, enableness and development socialize. From knowable field documentation data and observation result that governmental policy to ask Mayor or regent overflow some of kewenangannya [of] [at] Sub-Regency chief to draw near service of society have started felt by society. This matter is felt by subdistrict Kandis society, where they [is] served by IPTD On duty Kependudukan Civil kerumah Service and, specially in order to Act of birth publication. Result of interview with Head UPTD On duty Kependudukan civil Note and obtained by information that with role kordinasi played by Diinas by UPTD [is] salahsatunya UPTD Disduk Capil so that the child which have age [to] 0-18 year have more 90 % have